(untitled) (Historia, 2021)
Anton van Wouw : the smaller works is, as its title implies, concerned with the generally lesser-known smaller works of Dutch-born sculptor, Anton van Wouw. Using the measure of "half life-size and smaller" as a guideline, author Alexander Duffey provides a comprehensive and well-illustrated overview of the many full-length small sculptures, busts, relief panels and maquettes produced by Van Wouw between 1881 (nine years prior to his arrival in South Africa at the age of 28) and 1940. Naturalistically sculpted and generally cast in bronze, these smaller works are wide-ranging in their subject matter, depicting innocuous, commonplace scenes alongside aspects of Afrikaner history, representations of Boer and British leaders, and so-called "native studies" (p 11).